KOMPETENSI KEPALA DESA DALAM PERENCANAAN PEMBANGUNAN DESA DI DESA MERENG KECAMATAN WARUNGPRING KABUPATEN PEMALANG PROVINSI JAWA TENGAH - Muhaemin, Yosi; Hardian, Dafyar Eliadi; Mulyadi, Edi (Perspektif : Jurnal Ilmu Administrasi, 2025)
Abstrak This research aims to analyze the Village Head’s Competence in Village Development Planning in Mereng Village, Warungpring Sub-district, Pemalang Regency, covering the Village Head's knowledge, skills, and attitude, as well as the influencing factors and challenges in the village development planning process.The research method used is a qualitative approach with data collection techniques through observation, documentation, and in-depth interviews with informants from the village government and community elements. Data credibility and validity were tested using triangulation, specifically both technical and source triangulation. The research findings indicate that the Village Head possesses inadequate competence in village development planning. Inconsistencies were found among planning documents, along with minimal official documentation, and a lack of utilization of the village information system. In terms of technical and managerial skills, the Village Head demonstrated initiative but still faced administrative constraints, weak team coordination, and limitations in technology use. Regarding attitude, the Village Head showed commitment and responsibility toward development, but challenges persisted, including local political pressure, low community participation, and minimal involvement of vulnerable groups in planning. The conclusion of this study is that the Village Head's competence is at a basic functional level and is not yet professionally and systematically structured. Therefore, the research recommends continuous capacity building, regulatory assistance, and strengthening of the documentation system to achieve participatory, transparent, and sustainable village development. Keywords: Village head competencies, village development planning, knowledge, skills, attitudes, Mereng Village.